Blooms of the blue-green alga Cylindrospermopsis raciborskii in Emilia Romagna region (Italy): case reports managed by the Regional Agency for Environmental Protection and Energy of Emilia Romagna (ARPAE) - Michela Del Pasqua; Fabrizio Bandini; Elena Morandi; Rita Antonellini; Marcello Masi; Michele de Gioia (Advances in Oceanography and Limnology)
Cylindrospermopsis raciborskii is a toxic cyanobacterium that can form blooms potentially harmful to humans and animals. The proliferation of this species is difficult to predict, and its blooms are hard to detect as they cause just a moderate change in water colour. Global warming might increase the incidence of its proliferation worldwide. This trend was observed also by ARPAE that detected a growth in the presence of this alga in Emilia Romagna lakes and reservoirs in the last three years. This note describes the monitoring activities conducted by ARPAE during these algal blooms and the risk management actions implemented.